2022
DOI: 10.1101/2022.05.19.492617
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatiotemporal organization of human sensorimotor beta burst activity

Abstract: Beta oscillations in human sensorimotor cortex are hallmark signatures of healthy and pathological movement. In single trials, beta oscillations include bursts of intermittent, transient periods of high-power activity. These burst events have been linked to a range of sensory and motor processes, but their precise spatial, spectral, and temporal structure remains unclear. Specifically, a role for beta burst activity in information coding and communication suggests spatiotemporal patterns, or travelling wave ac… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 82 publications
0
10
0
Order By: Relevance
“…The strategy employed by our burst detection method deviates from those commonly used in the field. A global threshold on beta amplitude or power is most commonly used, often based on a centrality measure (mean or median beta amplitude), calculated from the whole dataset (Bonaiuto et al, 2021; Brady & Bardouille, 2022; Diesburg et al, 2021; Enz et al, 2021; Feingold et al, 2015; Kehnemouyi et al, 2021; Little et al, 2019; Shin et al, 2017; Wessel, 2020; Zich et al, 2022), or a percentile of the beta power distribution (Anidi et al, 2018; Cagnan et al, 2019; Pauls et al, 2022; Sherman et al, 2016; Tinkhauser, Pogosyan, Tan, et al, 2017; Torrecillos et al, 2018; Yeh et al, 2020). The consequence of these approaches is that only high amplitude burst events are detected, neglecting low amplitude, but potentially informative bursts.…”
Section: Discussionmentioning
confidence: 99%
“…The strategy employed by our burst detection method deviates from those commonly used in the field. A global threshold on beta amplitude or power is most commonly used, often based on a centrality measure (mean or median beta amplitude), calculated from the whole dataset (Bonaiuto et al, 2021; Brady & Bardouille, 2022; Diesburg et al, 2021; Enz et al, 2021; Feingold et al, 2015; Kehnemouyi et al, 2021; Little et al, 2019; Shin et al, 2017; Wessel, 2020; Zich et al, 2022), or a percentile of the beta power distribution (Anidi et al, 2018; Cagnan et al, 2019; Pauls et al, 2022; Sherman et al, 2016; Tinkhauser, Pogosyan, Tan, et al, 2017; Torrecillos et al, 2018; Yeh et al, 2020). The consequence of these approaches is that only high amplitude burst events are detected, neglecting low amplitude, but potentially informative bursts.…”
Section: Discussionmentioning
confidence: 99%
“…It is tempting to speculate that spatially dominant generators of the alpha rhythm could have large (co) kurtosis and result from bursting events. Recent work on bursting events also showed that bursting events propagate spatially across the cortex in a medial to lateral and anterior-posterior direction 61 . After application of k-means clustering, clear resting-state networks can be observed in both beta and alpha frequency bands, including the sensorimotor, visual, and default mode network.…”
Section: Discussionmentioning
confidence: 99%
“…a similar gradient in the medio-lateral axis of the STN. These variations suggest the presence of two distinct functional beta networks that control and gate the temporal integration of sensorimotor information in the cortex 37,52,53 .…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have demonstrated that sensorimotor β power preceding and following a movement exhibits distinct spatiotemporal and anatomical characteristics 35 . Building upon this knowledge, we sought to determine whether β t-SPC events during the ITI and the rebound phase during speech similarly exhibit distinct functional roles (Figure 6).…”
Section: Distinct Physiological Fingerprints Of Pre-and Post-speech P...mentioning
confidence: 99%